Diseño e implementación de una solución multitarea para un dispositivo IoT - ESP32 de medición de variables termodinámicas y eléctricas en tiempo real de un refrigerador doméstico 372 LRT F380G TMF (2023)
This work is related to specific objective 1 of a VCTI2024-1 Research Project on the real performance of a 372 LRT F380G TMF domestic refrigerator. The stated objective is the development of a multitasking solution that guarantees the real-time operation of an IoT- EPS32 device for measuring thermodynamic and electrical variables of a domestic refrigerator. With ESP32 technology, using the Wokwi simulation software and carrying out an analysis of the operation of the IoT-ESP32 device, data acquisition tasks, keyboard attention, visualization, and communications between the two cores that make it up were implemented, representing 30% reduction in task execution time in relation to a conventional single-core solution.